ISLAM AND STATE’S LEGAL PLURALISM: The Intersection of Qanun Jinayat and Criminal Justice System in Indonesia - Afandi, Fachrizal; Bagaskoro, Ladito Risang (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2024)
The article seeks to investigate the intersection of local-based religion legal system and state’s legal system. It focuses on the constitutional debates on the position and the status of Aceh Qanun Jinayat within the Indonesian legal system and how the Indonesian Supreme Court the Islamic penal law based on Aceh’s Qanun in their decisions. Using the legal research approach, this article begins with the background of the Qanun Jinayat implementation in Aceh, then discusses the constitutional debates on the position of the Qanun in the Indonesian legal system and ends with analyses of Supreme Court decisions on the application of the Qanun Jinayat in criminal cases in Aceh. This article argue that Aceh’s Qanun is similar to the other provincial regulation within the Indonesian legal system, which has limited areas to regulate the punishment in criminal cases. However, the paper found that although the Indonesian legal system forbids Aceh’s Qanun holds the penalty more severe than the National criminal law, the Supreme Court seems to accept these practices and use them in their decisions in Aceh’s criminal cases.